Meta-Analysis: Obesity, Smoking, and Alcohol Consumption as risk Factors of Breast Cancer - Yuliana Yuvrista; Wiwit Marliana (Journal of Epidemiology and Public Health, 2022)
Background: Breast cancer is a type of cancer that is the main cause of death in women. Breast cancer is classified as a non-communicable disease that requires a long time for the development of cancer cells in the patient's body with various risk factors that are multifactorial. Several incidences of breast cancer are often associated with risk factors for an unhealthy lifestyle, including frequent consumption of fast food, less consumption of fruits and vegetables, lack of exercise, alcohol consumption, etc. This study aims to analyze the effect of obesity, smoking, and alcohol consumption on the risk of breast cancer in women.Subjects and Method: This study used a systematic review of meta-analysis. Data search was carried out using electronic databases consisting of: PubMed, Science Direct, Europe PMC and Google Scholar with the search keywords used were "obesity" OR "BMI" AND "smoking" OR "smoking habit" AND " alcohol” OR “alcohol consumption” OR “alcohol intake” AND “breast cancer”. Inclusion criteria were full text articles in English with case control studies collected using PRISMA guidelines, and analyzed using the Review Manager application (RevMan 5.3).Results: A meta-analysis of 9 case-control study articles originating from Europe, North America, South America, Africa, and Asia showed women with obesity had a 3.53-fold increased risk of breast cancer compared with women of normal weight (aOR= 3.53; 95%CI= 2.70 to 4.62; p<0.001). A meta-analysis of 6 case-control study articles from Europe, North America, and, Asia showed that women who smoke have a 2.62 times higher risk of breast cancer compared to women who did not smoke (aOR= 2.62; 95%CI= 1.98 to 3.46; p<0.001). A meta-analysis of 7 case-control study articles originating from the continents of Africa, North America, South America, and, Europe showed that women who consume alcohol have a 3.62 times higher risk to have breast cancer compared to women who did not consume alcohol (aOR= 3.62; 95%CI= 2.31 to 5.69; p<0.001).Conclusion: Obesity, smoking and alcohol consumption are risk factors for breast cancer. Keywords: obesity, smoking, alcohol consumption, breast cancer Correspondence:Yuliana Yuvrista. Diploma IV of Midwifery, Universitas Ngudi Waluyo. Jl. Diponegoro 186, Ungaran 50512, Central Java, Indonesia. Email: yulianayuvrista031@gmail.com. Mobile: 085333622880.